The Comparative Analysis of the Legal Implications of Hadhanah in Decision Number 2562/Pdt.G/2023/PA.Sbr and Decision Number 0037/Pdt.G/2016/PA.Bitg in the Perspective of Maqaṣid al-Syari’ah - Ishak Lubis; Abdul Aziz Aziz (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
This study examines the differences in the determination of custody rights in the Sumber Religious Court decision No. 2562/Pdt.G/2023/PA.Sbr and the decision of the Bitung Religious Court Number 0037/Pdt.G/2016/PA.Bitg, even though both refer to the Compilation of Islamic Law (KHI). The divergence arises due to variations in trial facts, the child’s psychological condition, and the religious beliefs of the parties involved. Therefore, an analysis from the perspective of maqāṣid al-sharī’ah is essential to ensure that custody rulings not only adhere to normative provisions but also safeguard the child’s welfare. The main objectives of this research are to analyse the application of custody law in both cases and to compare them within the framework of maqāṣid al-sharī’ah. The research problems addressed are: (1) How was custody law applied in the Sumber and Bitung Religious Court decisions? and (2) How do these decisions differ when examined through the lens of maqāṣid al-sharī’ah? Using a normative juridical method with comparative and case study approaches, data were collected from legislation, Islamic legal scholarship, and official court rulings. Findings reveal that the Sumber Court prioritised maternal attachment and piety, while the Bitung Court prioritised protection of faith by granting custody to the father.